MOHO AND LOWER CRUSTAL REFLECTIVITY BENEATH A YOUNG RIFT BASIN - RESULTS FROM A 2-SHIP, WIDE-APERTURE SEISMIC-REFLECTION EXPERIMENT IN THE VALENCIA TROUGH (WESTERN MEDITERRANEAN) - Collier, J; Buhl, P; Torne, M; Watts, A (1994)
The paper presents new images of the lower crust and Moho beneath the Valencia Trough - a young rift basin in the western Mediterranean. Thse images show several features not distinguishable on previously available conventional single-ship reflection profiles. The Moho, which was previously only seen intermittently, can now be confidently traced throughout the basin. A present day depth-to-Moho map has been constructed and the degree of crustal thinning estimated for the whole basin. Crustal thinning is at a maximum in the centre of the basin, where β values reach 3.15±0.25. At the margins of the basin the β values decreases to 1.5±0.1. The reflective character of the lower crust and Moho is different beneath different parts of the basin. These differences have been correlated with the amount of stretching. The variations of the observed lower crustal reflectivity are interpreted as having been caused by the most recent (Neogene) stretching event that opened the Valencia Trough. -from Authors